SEBERAPA EFEKTIFKAH ARTIFICIAL INTELLIGENCE DALAM FRAUD DETECTION PADA MASA COVID-19: SYSTEMATIC LITERATURE REVIEW - Silvia Agustina; Putu Putri Risma Wandansari (Jurnal Aplikasi Akuntansi, 2023)
The development of increasingly advanced technology certainly has a positive impact in various fields, especially in auditing, especially during and after Covid 19. A technology that is most highlighted today is the use of Artificial Intelligence in detecting digital fraud risks, which can be interpreted as using the technology-based web to commit fraud and misuse of assets for financial gain. This study aims to review the use of AI in fraud detection to support external audits, especially during the Covid 19 period. The research method used in this study is a Systematic Literature Review (SLR) or systematic literature review. Based on the analysis results, Artificial Intelligence (AI) has begun to be applied to audit procedures to support decision-making through machine learning. The success of Artificial Intelligence in detecting fraud and issuing audit opinions must be seen as two complete sides, namely, opportunities and challenges that must be responded to wisely, especially by auditors. During the covid 19 pandemic, AI helps, especially for auditors challenged in creating new methods developed due to the required COVID-19 strategy. This research implies that auditors and companies can switch to using AI, which can help their work efficiency in disclosing fraud that occurs.